Studi Sosiologis Dakwah Digital dan Kesalehan Sosial Muslim di Semarang - Ervanto, Wachid; Mochtar, Asmaji; Siddik, Syahril (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Digital da'wah that has grown through social media and various technological platforms has become an effective means of disseminating Islamic values and fostering social awareness among Muslims in Semarang, Central Java. Using a qualitative approach, this study explores the experiences of preachers, social media managers, and da'wah followers to understand how technology-based religious outreach influences their religious practices. The findings reveal that all respondents perceived tangible benefits from digital da'wah. They reported gaining a deeper understanding of Islamic teachings and feeling more motivated to participate in social activities. Approximately 40% of communities adopted short video content as their primary strategy for delivering religious messages, while Instagram emerged as the most frequently used platform, accounting for 38%. Additionally, 60% of the audience expressed greater enthusiasm for engaging in religious social activities promoted through digital channels. Despite these positive outcomes, several challenges persist. A small portion of respondents (20%) noted algorithm-related constraints that limited the reach of their da'wah content. Overall, the study indicates that digital da'wah holds significant potential to strengthen social piety within the community. However, broader impact requires enhanced creativity and adaptability in responding to the rapid development of digital technologies.